Analisis Pola Komunikasi Organisasi pada Iyashi Reflexology Pakuwon Trade Center Surabaya - Kyla Azalis Prasetio; Hilda Yunita Wono (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
Good communication is necessary in running a business, so that each member can fulfill their role properly. This research examines the organizational communication patterns at Iyashi Reflexology Pakuwon Trade Center, a reflexology service with a Japanese-style concept that attracts consumers. Despite having an interesting concept, the organization still faces internal communication problems that affect operational effectiveness. This research aims to find out the communication patterns applied in the organization. The research used a qualitative approach with a case study method. Data were obtained through in-depth interviews with four informants, namely managers, admins, therapists, and customers, as well as supporting documentation. Data analysis was conducted with the help of NVivo software by doing open coding, axial coding and selective coding. The results showed that the communication pattern at Iyashi is a combination of wheel and all-channel communication patterns, which researchers call the hexaflow communication pattern. This pattern allows for centralized coordination as well as open communication between members. Hexaflow provides flexibility in information exchange, adapts to work situations and conditions, and helps minimize miscommunication within the organization. This finding can be a reference for encouraging the development of organizational communication standards in the direct service-based service sector.